Transient cleavage kinetics of the Eco RI restriction endonuclease measured in a pulsed quench-flow apparatus: enzyme concentration-dependent activity change. - Langowski, J (1981)
We report measurements of the cleavage rate of pBR 322 plasmid DNA by the restriction endonuclease Eco RI as a function of enzyme and DNA concentration. The reaction, which at high excess of enzyme over DNA occurs between 0.2 and 5 seconds, was studied by the means of a microprocessor controlled pulsed quench-flow apparatus. Enzyme concentrations were between 1 and 100 nM with DNA concentrations being 3 to 6 nM (specific Eco RI sites). The catalytic constants for cleavage of the first and second phosphodiester bonds as measured at high enzyme concentration both have the same value of 0.35 sec-1 and 21 degrees C. At enzyme concentrations comparable to or less than DNA concentration, the rate of the first cleavage is proportional to enzyme concentration, while the second step is independent of concentration. At approx. 10 nM Eco RI endonuclease concentration, a rate increase shows up in both the first and the second cleavage. We suggest that this increase is due to the tetramerization reported by Modrich & Zabel1, which occurs in this concentration range.